Thyroxine and Free Thyroxine Levels in Workers Occupationally Exposed to Inorganic Lead - Michael L. Bledsoe; Lynne E. Pinkerton; Sharon Silver; James A. Deddens; Raymond E. Biagini (SAGE Publishing, 2011)
Background The effects of lead exposure on thyroid function are unclear. Methods Serum thyroxine (T4) was evaluated among 137 lead-exposed workers and 83 non-exposed workers. Free thyroxine (FT4) was evaluated among a subset of these workers. Exposure metrics included blood lead level (BLL), which reflects recent exposure, zinc protoporphyrin (ZPP), a marker of intermediate-duration lead exposure, exposure duration, and estimated cumulative exposure. Multiple linear regression results were adjusted for age, race, and current smoking status. Results Mean BLLs were 38.9 μg/dL in lead exposed workers and 2.1 μg/dL in non-exposed workers. The adjusted mean T4 and FT4 concentrations among exposed and non-exposed workers were similar. While T4 was not significantly related to any of the exposure metrics, FT4 was inversely related to the logged values of both exposure duration and cumulative exposure, but not to ZPP or BLL. Conclusions The findings suggest that FT4 levels may be related to long-term lead exposure.